Nǣothāng kānbō̜rihān khwāmsīang kānphatthanā khrōngkān phalit faifā dūai phalangngān chīwamūan (Mūnnithi Phalangngān phư̄a Singwǣtlō̜m, 2009)
Guidelines on risk management of biomass power project development in Thailand.